Academic Self-Efficacy As Predictor Of Academic Achievement - Abd Basith; Andi Syahputra; Muhammad Aris Ichwanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
The purposes of this research are 1) to analyze the differences of the effect of gender, years of study, and major on the academic self-efficacy, and 2) to predict academic self-efficacy in determining academic achievement. This is a quantitative research using a survey approach. The location of this study is STKIP Singkawang (School of Teacher Training and Educational Science). The sample used is 223 students, which consisted of 112 males and 111 females. The data collection technique used is a questionnaire using a Likert scale. The data were analyzed using SPSS with descriptive statistical techniques, correlation, regression, and univariate GLM analysis. The results confirm that; 1) different majors have a significant influence on academic self-efficacy compared to the gender and years of study. The students of social sciences major have higher academic self-efficacy than those in the exact sciences major.; 2) self-efficacy has a positive relationship and is also a predictor in determining academic achievement. This shows that any improvement in academic self-efficacy will be accompanied by an improvement in the academic achievement.